DIAGNOSTIC VALUE OF ADDITIONAL MARKERS FOR ACUTE KIDNEY INJURY IN PRETERM NEONATES WITH PATENT DUCTUS ARTERIOSUS - О. Оболонська; Т. Мавропуло; Л. Вакуленко; Т. Борисова; О. Оболонський (Bukovynian State Medical University, 2023)
Acute kidney injury (AKI) is a common complication with high mortality rates among preterm infants at neonatal intensive care units. Identifi cation of preterm newborns who are at risk for developing AKI is essential not only for early diagnosis and treatment, but also for prevention since AKI signifi cantly worsens an outcome of any disease. Studying the information content of additional non-invasive markers for AKI, in particular, parameters of regional renal oxygen saturation (RrSO2) and Doppler estimation of blood fl ow in the main renal vessels is interesting. The aim of the study was to evaluate the diagnostic performance of additional markers (measurements of RrSO2 and blood fl ow in the main renal vessels using Doppler ultrasonography) in diagnosing of AKI and its degree of severity in preterm newborns with patent ductus arteriosus (PDA). Material and methods. A single- center, open, prospective cohort study examined 66 preterm infants born at 29-36 weeks of gestational age (GA) undergoing treatment at the Department of Anesthesiology and Intensive Care for newborns. Inclusion criteria: preterm newborns born between 29-36 week's gestation with hemodynamically signifi cant PDA (hsPDA), a written informed consent to participate in this study provided by parents. Exclusion criteria: congenital malformations, grades III-IV intracerebral or intraventricular hemorrhages, neonatal sepsis, severe perinatal asphyxia, skin diseases, fetal growth restriction. Clinical examination and treatment of children was carried out according to current guidelines. The modifi ed neonatal KDIGO criteria were used to diagnose and characterize the severity of AKI. Doppler ultrasound measurements were done to reveal the presence, size, and hemodynamic signifi cance of PDA. Color Doppler ultrasonography was performed to evaluate intrarenal hemodynamics upon hospital admission of children prior to prescribing ibuprofen, and in the case of hsPDA detection - on the 3rd and 10th days of life. Blood fl ow in the area from the main renal artery to the interlobar renal artery of the right kidney was measured including peak systolic velocity (PSV), end diastolic velocity (EDV), and the resistive index (RI) was calculated. RrSO2 values were recorded using near-infrared spectroscopy (NIRS) and renal fractional tissue oxygen extraction (rFTOE) was estimated within 24 hours on the 1st, 3rd and 10th days of life. The study received a positive conclusion of the Biomedical Ethics Commission of Dnipro State Medical University (minutes of the Commission meeting No. 8 dated 04.26.2023), which considered the scientifi c study as being consisted with generally accepted norms of morality, human rights requirements, interests and personal dignity of the study participants, bioethical standards of work with pediatric patients. There was no risk for study participants when performing examinations. Legal guardians of the children enrolled in the study were informed about all aspects related to the purpose, tasks, methods and expected benefi ts of the study. Laboratory and instrumental methods of examinations were generally adopted, medicines planned to be prescribed were licensed for use. Experiments with human subjects were not carried out. Statistical processing of the results was realized using a software product STATISTICA 6.1® (StatSoft Inc., serial number AGAR909E415822FA). A set of statistical analysis methods based on parametric and non-parametric criteria was used for solving the tasks of testing a hypothesis on diff erences between mean values, methods of assessing the eff ect with an alternative form of a reaction result, correlation analysis (Spearman's rank correlation), cluster analysis. The study was conducted within the bounds of complex research activities at the Department of Propaedeutics of Children's Diseases and Pediatrics No. 2 of Dnipro State Medical University "Development of criteria for early diagnosis and prediction of comorbid kidney damage in children with somatic and infectious diseases" (state registration number 0119U100836), the study period 09.2019-12.2023. Results. Group 1 (with moderate renal impairment) included 43 patients with a GA of 33.27±0.43 weeks. AKI was detected in 12 patients (27.9%), of those, 10 (23.3%) children developed stage 1 AKI according to the modifi ed neonatal KDIGO criteria, and stage 2 AKI were classifi ed in 2 (4.7%) patients. Group 2 was composed of 5 patients (infants with severe renal impairment) with a GA of 31.60±0.75 weeks. All the children in this group had diff erent stages of AKI (stages 1-3), which progressed to acute renal failure after 7 days. Mortality in this group was 60%. Group 3 consisted of 18 patients (infants with mild renal impairment) with a GA of 32.86±0.29 weeks. AKI stage 1 was diagnosed in 2 (11.1%) patients, and AKI was not detected in 16 (88.9%) of them. On the 1st day of life, the PSV and EDV values of the interlobar artery in children of the group with mild renal impairment were higher than those in children with a severe course of the disease (p<0.05). This trend regarding PSV continued on the 3rd day. Doppler parameters of renal blood fl ow, namely a decrease in EDV of the interlobar artery to 1.96 ± 2.22 cm/s and PSV to 8.14 ± 2.71 cm/s on the 1st day of life, as well as a decrease in PSV to 17,60 ±3.82 cm/s, EDV to 3.40±0.82 cm/s and increased RI up to 0.80±0.04 of the main renal artery were found to be early non-invasive predictors of severe AKI in preterm newborns on day of life 1 (p<0.05). Non-invasive monitoring of RrSO2 and calculation of rFTOE revealed a decrease in renal oxygenation by NIRS in preterm infants with PDA on the 1st day of life to 53.60 ± 1.11%, as well as rFTOE values of 0.45 ± 0.01, that was prognostically unfavorable with regard to the course of AKI (p<0.05). The highest value of RrSO2 on day 10 (91.8±0.81%) and the lowest rFTOE value (0.05 ± 0.01) (р<0.05) might indicate irreversible changes associated with reduced oxygen utilization due to destruction of cells and be used as a screening tool to detect and assess ductal steal phenomenon caused by hsPDA and the development of AKI. Conclusions. A decrease in the rate of diuresis within the fi rst 5 days of life as well as a two fold increase in the level of serum creatinine on postnatal days 3 and 10 were the main, but late markers for the development of severe kidney impairment in preterm newborns. Doppler parameters of renal blood fl ow, namely decreased EDV and PSV in the interlobar artery on the 1st day of life, and decreased PSV, EDV and increased RI in the main renal artery has been found to be early non-invasive predictors of severe AKI in preterm newborns on the 1st day of life. Non-invasive monitoring of RrSO2 and calculation of rFTOE can serve as screening tools for detection and assessment of hsPDA-related ductal steal phenomenon and the development of AKI.